1996
DOI: 10.1046/j.1365-2249.1996.d01-633.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between expression of antibodies to histone H2B and clinical activity in HIV-infected individuals

Abstract: SUMMARYLevels of autoantibodies specific for the histone, H2B, were measured in individuals with HIV infection. In comparison with normal (uninfected) controls, infected patients, particularly those with symptomatic disease, had significantly elevated titres of anti-H2B antibodies. Longitudinal studies confirmed that levels of these antibodies were highest in patients with lymphadenopathy and declined with the development of AIDS. In preliminary experiments designed to determine the biological significance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…HIV-1 infection is characterized by a plethora of autoimmune phenomena caused by the extreme immune activation. A high prevalence of circulating autoantibodies against a constellation of antigens has been reported in HIV-1-infected patients [5][6][7][8], but their clinical significance is unclear [9]. In a recent report, 2 AIDS patients with anemia caused by pure red cell aplasia (PRCA) responded favorably to prednisone treatment, suggesting the presence of an autoimmune mechanism [10].…”
mentioning
confidence: 99%
“…HIV-1 infection is characterized by a plethora of autoimmune phenomena caused by the extreme immune activation. A high prevalence of circulating autoantibodies against a constellation of antigens has been reported in HIV-1-infected patients [5][6][7][8], but their clinical significance is unclear [9]. In a recent report, 2 AIDS patients with anemia caused by pure red cell aplasia (PRCA) responded favorably to prednisone treatment, suggesting the presence of an autoimmune mechanism [10].…”
mentioning
confidence: 99%
“…Different studies reported a high prevalence of circulating autoantibodies, ranging from 4% for non-organ specific autoantibodies 11 to 47% for histone H2B autoantibodies. 12 However, these studies failed to show clinical significance for any of these autoantibodies. 13 On the contrary, in a previous study 14 we have shown that among HIV-infected patients, circulating anti-EPO autoantibodies were independently associated with lower hemoglobin and higher erythropoietin levels.…”
Section: Discussionmentioning
confidence: 95%
“…The lack of binding of LG11-2 to this analogue suggests that the terminal residues of the 6 -18 peptide may be involved in direct contact with the LG11-2 binding site or that some of these residues (e.g. Pro 8 , which was replaced in R1 by an acetylated alanine) play a critical role in the overall conformation of the epitope.…”
Section: Resultsmentioning
confidence: 99%
“…Among antibodies to individual core histones, those reacting with histone H2B are a particularly frequent specificity (3)(4)(5)(6). Antibodies to H2B are also encountered in other autoimmune diseases, such as systemic sclerosis (7) as well as in human immunodeficiency virus-infected individuals (8). Anti-H2B antibodies in SLE patients almost always recognize determinants that are located in the amino terminus (residues 1-25) of the histone molecule (9).…”
mentioning
confidence: 99%